The experience of remote recruitment for Essential Coaching for Every Mother during the coronavirus disease 2019 pandemic. Issue 3 (15th December 2021) - Dol, Justine; Murphy, Gail Tomblin; McMillan, Douglas; Aston, Megan; Campbell-Yeo, Marsha
ABSTRACT: Introduction and aims: Due to physical distancing recommendations because of the COVID-19 pandemic, recruitment approaches for perinatal research needed to shift from in-person to remote. The purpose of this study is to describe the recruitment and retention of women for an mHealth intervention study for Essential Coaching for Every Mother. Methods: Three methods were used for recruitment: social media, posters in hospital, and media outreach. First time mothers were eligible for enrollment antenatally (37+ weeks) and postnatally (<3 weeks). Eligibility screening occurred remotely via text message. Outcomes were days to recruit 75 participants, eligibility vs. ineligibility rates, dropout and exclusion reasons, survey completion rates, perinatal timing of enrollment, and recruitment sources. Results: Recruitment ran from 15 July to 19 September 2020 (67 days) with 200 potential participants screened and 88 enrolled. It took 50 days to enroll 75 participants. Women recruited antenatally were more likely to receive all intervention messages (68 vs. 19%) and miss fewer messages (6.4 vs. 13.8) than women enrolled postnatally. Participants heard about the study through family/friends (31%), news (20%), Facebook groups/ads (30%), posters (12%), or other (7%). Conclusion: Antenatal recruitment resulted in participants enrolling earlier and receiving more messages. Remote recruitment was a feasible way to recruit, with word of mouth and media outreach being most successful, followed by Facebook.